DIAGNOSTICS OF DOG ANAPLASMOSIS - Levytska, V. A.; Berezovskyi, A. V.; Mushynskyi, A. B. (Scientific Progress & Innovations, 2020)
Granulocytic anaplasmosis is a disease caused by small obligate intracellular bacteria of the Rickett-siales series, namely Anaplasma phagocytophilum, transmitted by ticks. People, dogs, cats, horses, sheep, goats, cattle, llamas can suffer from it. Diagnostics of dog anaplasmosis is usually based on analyzing epi-zootic data, clinical signs, hematological, biochemical, serological tests and, PCR. The research was con-ducted in the veterinary clinic “Fauna-Service”in Kamyanets-Podilsky, Khmelnytsky region during 2018-2019. Dogs of different ages, breeds and sexes were examined in the clinic. The study included 13 dogs with a positive PCR result on the DNA of A. phagocytophilum. All 13 dogs had an acute form of the disease. Most dogs had nonspecific clinical signs such as indolence and decreased motional activity. Diarrhea and vomit-ing were rarely registered. During physical examination, the dogs were not active. Hyperthermia (from 39.7 to 41.2 °C), tachycardia and polypnea were recorded. Biochemical blood examination revealed a slight de-crease in total protein in 10 dogs (53.57±1.36 g/l) and albumin in 6 dogs (23.01±1.31 g/l). Hematological changes included thrombocytopenia in 11 dogs (110.95±5.71 x 109/l) and anemia in 8 dogs (erythrocyte number 4.55±0.36 x 1012/l; hemoglobin concentration 94.28±5.85 g/l; hematocrit: 32.92 %). Leukocytosis was also observed in 2 dogs (10.25±1.87 x 109/l). Besides, increased enzymes in 8 dogs and hyper-bilirubinemia in 5 dogs were the most common abnormalities. The concentration of bilirubin was above normal (23.98±6.65 μmol/l); alkaline phosphatase – 113.53±15.58 u/l, ALT – 117.74±14.44 u/l, AST – 70.98±9.15 u/l. Small oval basophilic intra-cytoplasmic inclusions (morulae) having the size of 2 to 3 μm, corresponding to A. phagocytophilum were found in neutrophils of blood smears of 9 dogs. Renal azotemia was observed in urine analysis of only some dogs. All 13 dogs were treated on an outpatient basis. For the final establishment and confirmation of the diagnosis, it is necessary to conduct blood test by PCR method. Thus, granulocytic anaplasmosis should be considered as a probable diagnosis in dogs during the period of tick activity in Khmelnytsky region.